2020
DOI: 10.11591/ijere.v9i4.20738
|View full text |Cite
|
Sign up to set email alerts
|

Guiding principles and practices of peace education followed in secondary schools of Mizoram

Abstract: <span>The significance of peace education is universally recognized for a safe and prospering future for the world at school level as peace education aims at equipping the future citizens with necessary knowledge, attitude and skills so that they would acknowledge and respect all kinds of diversity and understand human dignity. This paper is based on an empirical research aiming how far guiding principles and practices of peace education followed in secondary schools of Mizoram. The concept of peace educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 9 publications
(11 reference statements)
0
13
0
4
Order By: Relevance
“…Peace education is one of the educations that should exist and be developed in families, schools, and communities. This is because peace education aims to equip citizens with knowledge, attitudes, and skills on how to establish peace in society, as stated by [6] Education has become a tool for the world to transform generations. Since 1945, UNESCO has been working through education to promote international peace and the general welfare of mankind, including by improving the curriculum and teacher training [7].…”
Section: Peace Educationmentioning
confidence: 99%
“…Peace education is one of the educations that should exist and be developed in families, schools, and communities. This is because peace education aims to equip citizens with knowledge, attitudes, and skills on how to establish peace in society, as stated by [6] Education has become a tool for the world to transform generations. Since 1945, UNESCO has been working through education to promote international peace and the general welfare of mankind, including by improving the curriculum and teacher training [7].…”
Section: Peace Educationmentioning
confidence: 99%
“…From the two backgrounds, one can say peace education refers to that interdisciplinary area of education where both formal and non-formal approaches to teaching about peace and for peace are adopted or utilized for knowledge dissemination. Better still, peace education involves the promotion of knowledge, skills, attitudes and values that are needed to bring about behavioural changes among both youth and adults towards the prevention of conflicts both overtly and structurally (Mishra, 2020). A system that averts its attention to resolving conflicts peacefully as well as the creation of conditions conducive to peace at all levels-intrapersonal, interpersonal, intragroup, national and international (Fountain, 1999).…”
Section: Definition and Evolution Of Peace Educationmentioning
confidence: 99%
“…At this period, peace education programs were aimed mainly at halting the threat of nuclear war and arms race, which was later to inculcate environmental and development issues into the plan (Dugan & Carey, 1996;Najjuma, 2011). Immediately following this period, the events of terrorism, political instability in the Eastern European bloc, military takeovers in African States, and the increasing gap between developed and undeveloped world, created new challenges for the understanding of peace and the underlying principles of responsibility and security (Mishra, 2020). Today, scholarly works by many scholars have added a lot more impetus into what peace education is, and how through its practice, the culture of peace is attainable, globally and locally.…”
Section: Definition and Evolution Of Peace Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers should establish a culture of peace in schools and present themselves as role models of peace. They must resolve any problems and conflicts among themselves and among students through dialogue [11]. Kutlu and Bedel [3] found that the conflict resolution psycho-education program applied to adolescents increased their integration and compliance scores.…”
Section:  Issn: 2252-8806mentioning
confidence: 99%